Pratiques informationnelles des youtubeurs scientifiques au service de la médiation du savoir - Emmanuelle Chevry Pébayle (Communication)
Since its inception in 2005, YouTube has been a source of scientific and cultural information geared to the general public. Scientific content creators make money on their expertise and play an important role in mediating knowledge and/or bringing it to a wider audience. To better understand the relationship between science, research, and society, the author looks at how these “pro-am” (professional amateur) YouTubers view their work and their informational skills. The success of pro-am YouTubers seems to depend on an expert ethos that is no longer based solely on academic criteria such as the speaker’s academic degrees or profession.